2020
DOI: 10.1016/j.psj.2020.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Soybean oligosaccharide, stachyose, and raffinose in broilers diets: effects on odor compound concentration and microbiota in cecal digesta

Abstract: Soybean oligosaccharides have been previously shown to be associated with the production of major odor-causing compounds in broilers, although little is known about the role of stachyose and raffinose, which are key components of soybean oligosaccharide, in broiler cecal microbiota and odor compound production. To this end, soybean oligosaccharide, stachyose, and raffinose were added to the birds' diets to investigate their effects on odor compound production and the microbial community characteristics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 36 publications
10
42
1
Order By: Relevance
“…Based on the phylogenetic diversity of bacterial communities and number of OTUs, SBO and CHL did not change the chicken cecal bacterial community membership, but the treatments signi cantly altered relative abundance of certain taxa in the cecum. This observation is in accordance with the study of Zhu et al [30] who reported that SBO addition (0.6%) altered the chicken cecal microbiota. When added frucotooligosaccharide in broiler diets, the total number of anaerobes and Lactobacilli in the ceca increased while the number of E. Coli decreased [32].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Based on the phylogenetic diversity of bacterial communities and number of OTUs, SBO and CHL did not change the chicken cecal bacterial community membership, but the treatments signi cantly altered relative abundance of certain taxa in the cecum. This observation is in accordance with the study of Zhu et al [30] who reported that SBO addition (0.6%) altered the chicken cecal microbiota. When added frucotooligosaccharide in broiler diets, the total number of anaerobes and Lactobacilli in the ceca increased while the number of E. Coli decreased [32].…”
Section: Discussionsupporting
confidence: 93%
“…4) appeared to be diminished by chlortetracycline. These results are consistent with earlier observations that in-feed antibiotic preferentially enriched butyrate-producing bacteria [19], SBO inhibited the growth of pathogenic microbes, and reduced the production of odor compounds [3,14,30]. Previous studies have found that supplementation of broiler diets with a mixture of chlortetracycline and other antibiotic increased both Ruminococcaceae and Lachnospiraceae [34].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations